If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (3 + -2) = 9 Combine like terms: 3 + -2 = 1 x + (1) = 9 x + 1 = 9 Reorder the terms: 1 + x = 9 Solving 1 + x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 9 + -1 Combine like terms: 1 + -1 = 0 0 + x = 9 + -1 x = 9 + -1 Combine like terms: 9 + -1 = 8 x = 8 Simplifying x = 8
| X-6=18-3x | | 9-x=25 | | 5y-1=3y+13 | | 7/12x-7/6x^2 | | 117=2x^2+7+61-x^2 | | 6y-24=12 | | 7n+21+n=37 | | 5x=65+x | | 6-(x+4)=12 | | 6y+4x=20 | | (3z-1)-(z+2)=15 | | 1.75x+0.65=10 | | 1.75-0.65x=10 | | -3e=9e+7 | | 2x1/2=9/8 | | X^2-12x-3=14 | | 3ax+1=16 | | 0.4=.40 | | 5y=16[8] | | 36=2x+y | | z/7-3=2 | | x^2-33= | | -8(6x-2)+7(7x-7)-7=6-2 | | u/11=6 | | 11w=8470 | | -[7x+(6x+1)]=4-(5x+8) | | 6x^2-12x-51=-3 | | t+12=24 | | -4ln(x)+2x+6=0 | | 3tanx-5=4 | | 5k^2+12k+4= | | cos^2x+4cosx-5=0 |